In Their Own Voices - Jennifer Ann Morrow; Sharon Clayman; Bonnie McDonagh (SAGE Open, 2012)
It is estimated that child abuse and neglect result in direct (e.g., health care, law enforcement, judicial system) and indirect (e.g., special education, lost productivity to society) costs of approximately 103 billion dollars each year. Why do some abuse survivors display healthy functioning as adults while others display a variety of physical and psychological health problems? It was the goal of this study to discover what positive influences, both internal and external, that individuals relied on to overcome childhood trauma. Five main themes emerged from the data. The five themes are as follows: Spirituality/Faith in God, Supportive Others, Therapeutic Relationships, Self-Determination , and Expressive Writing . A description of these themes and selected quotes from participants are described.